2020
DOI: 10.1111/1467-8454.12174
|View full text |Cite
|
Sign up to set email alerts
|

Economic uncertainty, ownership structure and small and medium enterprises performance

Abstract: This paper investigates the effect of economic uncertainty on the performance of small and medium enterprises (SMEs) over the period 2007-2016. This paper also examines the effects of ownership structure on the relation between Economic Uncertainty and firm performance. We find that an increase in economic uncertainty is negatively associated with the performance of SMEs. Our results also reveal that increased economic uncertainty is associated with a lower performance level for state-owned SMEs, whereas forei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 105 publications
(162 reference statements)
0
16
0
Order By: Relevance
“…Economic obstacles are weak economy, tax burden, high exchange rate and lower purchasing power of consumer and high inflation rate. Doan et al (2020) found that an increase in economic uncertainty has a negative effect on entrepreneurial SMEs’ performance. With higher GDP per capita and a strong and developed financial system, developed countries report fewer financial and economic obstacles to entrepreneurial SMEs’ growth than less developed countries (Moder and Bonifai, 2017).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Economic obstacles are weak economy, tax burden, high exchange rate and lower purchasing power of consumer and high inflation rate. Doan et al (2020) found that an increase in economic uncertainty has a negative effect on entrepreneurial SMEs’ performance. With higher GDP per capita and a strong and developed financial system, developed countries report fewer financial and economic obstacles to entrepreneurial SMEs’ growth than less developed countries (Moder and Bonifai, 2017).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…In Eqn. (4), we introduce interaction terms between Happiness and FM20 , which is a dummy variable that takes a value of 1 if a firm is family-owned using the threshold of 20%, as suggested in prior studies (Nguyen, 2011a; Doan et al , 2020). We also include the same vector of control variables as in the baseline regression.…”
Section: Resultsmentioning
confidence: 99%
“…The year 1990 constituted the lower bound of the period studied since the first published and indexed article, whose title clearly presents the keywords "Ownership structure" and "performance", was the article by Smith (1990). The upper bound will be the month of June 2020 (date corresponding to the completion of the bibliographical research) with the articles by Doan, Le, and Tran (2020) and Kuo, Lu, and Dinh (2020) After eliminating the journals in which no articles are published with the combination of keywords used, and with the exclusion of books, papers and web pages, we were able to build a base of 229 articles published in 141 journals.…”
Section: Methodsmentioning
confidence: 99%